Electrochemical Synthesis of Microwave-Assisted Zinc Nanoparticles for Photocatalytic Degradation of Phenolic Compounds - Muhammad Farhan Hanafi; Norzahir Sapawe, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study explores the electrochemical synthesis of zinc nanoparticles using microwave-assisted technology for the photodegradation of phenolic compounds in aqueous solutions. The electrochemical method offers a simple, efficient approach for synthesizing zinc nanoparticles with enhanced catalytic properties. The microwave-assisted process significantly improved the nanoparticles' surface area, pore structure, and stability. The synthesized of mesoporous electrogenerated zinc nanoparticles (denoted MsEgZn) demonstrated excellent photocatalytic performance, achieving a 97% degradation of phenol within 60 minutes under optimal conditions. This approach offers a sustainable, cost-effective solution for removing toxic phenolic pollutants from water, with potential applications in environmental remediation.